A Diglossia Study of Sundanese Varieties among Sundanese Students: A Case Study of the Use of Sundanese Variety among University Students in the City of Bandung - Supian Supian; Alexandra Leonidovna Lebedeva; Ladinata Ladinata; Ruswan Dallyono; Renaldy Serby Yudistira (Master Program in Linguistics, Diponegoro University, 2025)
Sundanese Language is divided into two main varieties: high Sundanese variety (lemes) and low Sundanese variety (loma), each used in specific contexts. This study investigates the use of Sundanese varieties by Sundanese students in the city of Bandung. This research aims to identify and analyze the Sundanese language varieties and the factors influencing its use among students in the city of Bandung. This research used a qualitative approach. Therefore, the data were obtained from two WhatsApp groups, consisting of 192 members. The data collected in this research were in the form of WhatsApp conversations among Sundanese students. Based on the analyses, this research explored 34 instances of H (high) and 216 of L (low) of Sundanese variety. The H variety is typically appeared in conversations correlated with academic contexts or when the speaker is addressing a respected person. In contrast, the L variety is tend to be used in a more casual conversation with close friends and unrelated to academic contexts.